A preparation process of high performance aluminum bronze
By adding AlTiB and Al-Zr intermediate alloy to aluminum bronze, ultrasonic vibration and rotating magnetic field treatment are carried out, and a hydrophobic corrosion-resistant protective film is formed, the corrosion resistance and welding performance of aluminum bronze in the marine environment is solved, and the corrosion resistance and welding performance of aluminum bronze in the marine environment is significantly improved. Its strength and welding quality.
Patent Information
- Application Number
- CN202410553950.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-07
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-05-07
AI Technical Summary
Aluminum bronze is easily oxidized in the marine environment, and chloride ions destroy the oxide film, resulting in reduced corrosion resistance and poor welding performance, making it difficult to meet the high-performance requirements in the field of sea ships.
The high-performance aluminum bronze preparation process is adopted, and ultrasonic vibration treatment and rotating magnetic field electromagnetic treatment are performed by adding AlTiB and Al-Zr intermediate alloys to form a hydrophobic corrosion-resistant protective film, which improves the mechanical properties and welding quality of aluminum bronze.
It significantly improves the strength, toughness and seawater corrosion resistance of aluminum bronze, reduces welding defects, and improves welding quality and salt resistance.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum bronze production, and more specifically, to a preparation process of high-performance aluminum bronze. Background Art
[0002] Aluminum bronze is an alloy with aluminum as the main strengthening element. Its mechanical properties are higher than those of brass and tin bronze. It is generally used in gears, bushings, propellers, pumps, valve bodies, worm gears and other parts with high wear resistance and corrosion resistance. Although aluminum bronze can show excellent corrosion resistance in the atmosphere and fresh water, the aluminum in aluminum bronze is chemically active. Aluminum bronze is easily oxidized in air or humid environment, forming an oxide film on the surface of aluminum bronze. In the marine environment, due to the presence of chloride ions, the radius of chloride ions is small and the penetration is large, which makes it easy for chloride ions to destroy the oxide film on the surface of aluminum bronze and produce pitting, affecting the corrosion resistance of aluminum bronze. In addition, in the special application scenarios in the field of marine ships, the requirements for ship accessories are gradually increasing, resulting in an increasingly strong market demand for high-performance aluminum bronze, but most of the current aluminum bronze cannot meet this requirement. Therefore, it is urgent to further improve the mechanical properties of aluminum bronze, such as strength and toughness.
[0003] In addition, aluminum bronze has poor performance in welding, mainly because a dense and refractory aluminum oxide film is easily formed on the surface of aluminum bronze, covering the surface of the molten droplets and the molten pool, which easily produces defects such as slag inclusions, pores and unmelted warehouses in the weld, reducing the efficiency and quality of aluminum bronze welding and bringing certain challenges to the connection process. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a preparation process for high-performance aluminum bronze.
[0005] A preparation process of high-performance aluminum bronze, wherein the mass percentage of alloy components of the high-performance aluminum bronze is: Al: 7.0-13.0%, Mn: 4.0-8.0%, Fe: 2.0-4.0%, Ni: 1.0-4.0%, Ti: 0.2-0.8%, B: 0.1-0.3%, Zr: 0.06-0.2%, and the balance is Cu and unavoidable impurities;
[0006] The steps include:
[0007] S1: Melting: weighing the charge according to the alloy composition ratio of aluminum bronze, the charge including electrolytic copper, metal aluminum, manganese powder, iron powder, AlTiB master alloy, nickel plate and Al-Zr master alloy, adding the charge into a melting container and melting it into a melt;
[0008] S2: Ultrasonic vibration treatment, adding a slag remover to the melt for refining, performing ultrasonic vibration treatment on the melt during the refining process, and after the refining is completed, pouring the melt into a ladle, and obtaining an alloy melt after heat preservation, standing, and slag removal;
[0009] S3: Pouring and heat treatment: pouring the alloy melt into the casting mold, applying a rotating magnetic field on the left and right sides of the casting mold for electromagnetic treatment, then spraying water on the outer surface of the casting mold to cool it, and removing the solidified casting from the casting mold.
[0010] It is taken out and after heat treatment, aluminum bronze is obtained;
[0011] S4: Formation of a hydrophobic and corrosion-resistant protective film. After sandblasting, cleaning and etching the aluminum bronze, the nickel plate and the pretreated aluminum bronze are placed in an electroplating solution, and the aluminum bronze is subjected to an electroplating operation. After the electroplating operation, the aluminum bronze is immersed in an ethanol solution of ammonium ferrous sulfate, and then dried to complete the formation of a hydrophobic and corrosion-resistant protective film on the surface of the aluminum bronze, thereby obtaining high-performance aluminum bronze.
[0012] Furthermore, step S1 smelting specifically comprises the following steps:
[0013] S1.1: Weigh the furnace charge according to the alloy composition ratio of high-performance aluminum bronze, which includes electrolytic copper, metallic aluminum, manganese powder, iron powder, AlTiB master alloy, nickel plate and Al-Zr master alloy;
[0014] S1.2: Add electrolytic copper, metallic aluminum, manganese powder, and Al-Zr master alloy into a smelting container, and smelt in vacuum at 1260-1320°C for 30-50 minutes, stirring continuously during the melting, until the electrolytic copper, manganese powder, Al-Zr master alloy, and metallic aluminum are all melted;
[0015] S1.3: Subsequently, iron powder, nickel plate and AlTiB master alloy are added into the smelting container, and vacuum smelting is performed at 1600-1780° C. for 20-40 min, with continuous stirring, until all the materials in the smelting container are melted to obtain a melt.
[0016] Furthermore, in step S2.3, the ultrasonic radiation rod is made of stainless steel and the surface is covered with a layer of carbide to prevent corrosion by the aluminum melt.
[0017] Furthermore, step S2 of ultrasonic vibration treatment specifically includes the following steps:
[0018] S2.1: adding a slag remover to the melt, introducing nitrogen into the smelting container, and refining the melt for 5 to 8 minutes, wherein the mass ratio of the melt to the slag remover is 1:(0.001 to 0.003);
[0019] S2.2: During the refining process, turn on the ultrasonic drive power switch of the ultrasonic generator, immerse the ultrasonic radiation rod into the melt to a depth of 2 to 5 cm, and apply ultrasonic vibration with a power of 600 to 1000 W;
[0020] S2.3: After ultrasonic vibration treatment for 3 to 5 minutes, turn off the ultrasonic drive power switch of the ultrasonic generator and remove the ultrasonic radiation rod from the melt;
[0021] S2.4: After refining, pour the refined melt into a ladle, keep it at 1400-1500°C for 2-7 minutes, remove the slag, and obtain an alloy melt.
[0022] Furthermore, the slag remover in step S2.1 is at least one of calcium fluoride, aluminum chloride, sodium chloride, potassium chloride or aluminum oxide.
[0023] Furthermore, in step S2.2, the operating frequency of the ultrasonic generator is 20-25 KHz, and the maximum power is 3 KW.
[0024] Furthermore, step S3 of pouring and heat treatment specifically includes the following steps:
[0025] S3.1: Transfer the alloy melt to the pouring position of the casting machine, and then pour the alloy melt into the preheated casting mold;
[0026] S3.2: The rotating magnetic field generator and the three-phase voltage regulator are placed on the left and right sides of the casting mold. After the alloy melt is poured into the casting mold, the rotating magnetic field generator and the three-phase voltage regulator are started to apply a rotating magnetic field. The rotation rate of the rotating magnetic field is 78 to 82 r / s, and the rotation direction is changed once every 30 to 60 seconds. The rotation direction of the rotating magnetic field is changed by the three-phase voltage regulator. After electromagnetic treatment for 2 to 5 minutes, the rotating magnetic field generator and the three-phase voltage regulator are turned off;
[0027] S3.3: Then, spray water on the outer surface of the casting mold to cool it for 60 to 80 seconds;
[0028] S3.4: When the casting is solidified and cooled to a temperature of 300-320°C on the surface of the casting mold, the casting is taken out of the casting mold and placed in a resistance furnace and heated to 800-900°C for 1-3 hours. The casting is taken out of the furnace and placed in the air to cool, thus completing the high temperature heat treatment;
[0029] S3.5: When the casting temperature drops to 320-350°C, put the casting back into the resistance furnace and heat it to 430-480°C, keep it warm for 2-5 hours, take the casting out of the furnace and place it in the air to cool, thus completing the low-temperature heat treatment;
[0030] S3.6: When the temperature of the casting drops to 320-350°C, place the casting back into the resistance furnace and heat it to 520-600°C. Keep it warm for 1-3 hours. Take the casting out of the furnace and place it in the air to cool. After the casting cools to room temperature, aluminum bronze is obtained.
[0031] Furthermore, step S4 forms a hydrophobic and corrosion-resistant protective film, which specifically includes the following steps:
[0032] S4.1: putting the aluminum bronze into a dry sandblasting machine, passing 0.1-0.15 MPa compressed air and sand material into the spray gun of the dry sandblasting machine, sandblasting and polishing the surface of the aluminum bronze for 6-12 minutes, and then ultrasonically cleaning the aluminum bronze after sandblasting and polishing with deionized water for 3-5 minutes to obtain the aluminum bronze after surface treatment;
[0033] S4.2: Place the surface treated aluminum bronze and copper plate in a 0.2 mol / L NaCl aqueous solution, with the surface treated aluminum bronze as the anode and the copper plate as the cathode. The distance between the anode and the cathode is set to 30-40 mm. A DC power supply is applied with a current density of 0.2-0.5 A / cm 2 , magnetic stirring at 100-150 rpm / min, after etching for 3-5 minutes, taking out the etched aluminum bronze, and ultrasonically cleaning it with deionized water for 3-5 minutes to obtain the pretreated aluminum bronze;
[0034] S4.3: Add nickel sulfate, nickel chloride, boric acid, sodium saccharin, 1,4-butynediol and nano-silicon dioxide into deionized water, stir and mix well to obtain an electroplating solution;
[0035] S4.4: Place the nickel plate and the pretreated aluminum bronze in the electroplating solution, with the nickel plate as the anode and the pretreated aluminum bronze as the cathode. Set the distance between the anode and the cathode to 30-40 mm, heat to 50-60°C, and pass a DC power supply so that the current density is controlled at 4-5 A / dm 2 , magnetic stirring 150-200 rpm / min, electrodeposition 10-15 min;
[0036] S4.5: Subsequently, the electrodeposited aluminum bronze is taken out, washed with deionized water for 1 to 2 times, and then immersed in an ammonium ferrous sulfate ethanol solution with a concentration of 1 wt%. After soaking for 30 to 40 minutes, it is dried at normal pressure of 100 to 120°C for 15 to 20 minutes to complete the formation of a hydrophobic and corrosion-resistant protective film on the surface of the aluminum bronze, thereby obtaining high-performance aluminum bronze.
[0037] Furthermore, in step S4.3, the mass ratio of nickel sulfate, nickel chloride, boric acid, sodium saccharin, 1,4-butynediol, nano-silicon dioxide and deionized water is (20-25): (4-6): (3-8): (0.5-1.5): (7-13): (10-25): (200-300).
[0038] Furthermore, the nano-silicon dioxide used in step S4.3 has a particle size of 20 to 25 nm.
[0039] A high-performance aluminum bronze is prepared by the above-mentioned preparation process of the high-performance aluminum bronze.
[0040] The present invention has the following advantages:
[0041] 1. In the present invention, by adding AlTiB master alloy and Al-Zr master alloy, during the smelting process, Zr element can interact with Al element to form fine dispersed intermetallic compound particles Al3Zr, which effectively hinders recrystallization and grain growth, avoids the large grain phenomenon, and improves the strength and toughness of the alloy. Ti element and B element can form TiB2 during smelting, modify the alloy microstructure, inhibit the alloy recrystallization process, refine the alloy grains, form uniformly distributed fine grains in the alloy, and further improve the strength and toughness of the alloy.
[0042] 2. In the process of melt refining, the present invention performs ultrasonic vibration treatment on the melt, which can achieve the purpose of degassing, removing impurities and refining grains, further improve the composition uniformity and grain structure of the alloy melt, accelerate the diffusion rate of each component in the alloy melt, thereby improving the tensile strength and fracture resistance of the alloy, thereby improving the strength and toughness of aluminum bronze.
[0043] 3. In the present invention, under the action of a rotating magnetic field, the solidification structure of the alloy can be refined, so that the solidification structure in the aluminum bronze is a non-dendritic structure with a relatively uniform distribution, and dendrites growing in the longitudinal and transverse directions are suppressed and broken, and the solidification structure is distributed more evenly, and the grain spacing is significantly reduced, thereby further improving the tensile strength and fracture resistance of the alloy, and improving the strength and toughness of the aluminum bronze.
[0044] 4. In the present invention, a hydrophobic and corrosion-resistant protective film is formed by electroplating on the surface of aluminum bronze. The hydrophobic and corrosion-resistant protective film is composed of a composite of nano-silicon dioxide and nickel, so that the hydrophobic and corrosion-resistant protective film has the characteristics of corrosion resistance and bonding strength, and plays a hydrophobic and corrosion-resistant role on the aluminum bronze. The obtained high-performance aluminum bronze has good seawater corrosion resistance. Moreover, when welding high-performance aluminum bronze, the nano-silicon dioxide in the hydrophobic and corrosion-resistant protective film on the surface of the high-performance aluminum bronze can improve welding formation, reduce the occurrence of weld defects, and improve welding quality. DETAILED DESCRIPTION
[0045] In order to enable persons skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0046] Example 1
[0047] A preparation process of high-performance aluminum bronze, wherein the mass percentage of aluminum bronze alloy components is: Al: 13.0%, Mn: 5.0%, Fe: 4.0%, Ni: 3.0%, Ti: 0.8%, B: 0.3%, Zr: 0.2%, and the balance is Cu and unavoidable impurities;
[0048] The specific steps include:
[0049] S1: Smelting,
[0050] S1.1: Weigh electrolytic copper, metallic aluminum, manganese powder, iron powder, AlTiB master alloy, nickel plate and Al-Zr master alloy according to the alloy composition ratio of high-performance aluminum bronze;
[0051] S1.2: Add electrolytic copper, metallic aluminum, manganese powder, and Al-Zr master alloy into a smelting container, and smelt in vacuum at 1320°C for 50 minutes, stirring continuously during the melting, until the electrolytic copper, manganese powder, Al-Zr master alloy, and metallic aluminum are completely melted;
[0052] S1.3: Subsequently, iron powder, nickel plate and AlTiB master alloy are added to the smelting container, and vacuum smelting is performed at 1780°C for 40 minutes, with continuous stirring, until all the materials in the smelting container are melted, thereby obtaining a melt;
[0053] S2: Ultrasonic vibration treatment,
[0054] S2.1: adding a mixture of aluminum chloride, sodium chloride and aluminum oxide to the melt, introducing nitrogen into the smelting container, and refining the melt for 8 minutes, wherein the mass ratio of the melt to the mixture of aluminum chloride, sodium chloride and aluminum oxide is 1:0.003;
[0055] S2.2: During the refining process, turn on the ultrasonic drive power switch of the ultrasonic generator, immerse the ultrasonic radiation rod into the melt to a depth of 5 cm, and apply ultrasonic vibration with a power of 1000 W;
[0056] S2.3: After 5 minutes of ultrasonic vibration treatment, turn off the ultrasonic drive power switch of the ultrasonic generator and remove the ultrasonic radiation rod from the melt;
[0057] S2.4: After refining, pour the refined melt into a ladle, keep it at 1500°C for 7 minutes, remove the slag, and obtain an alloy melt;
[0058] S3: pouring and heat treatment,
[0059] S3.1: Transfer the alloy melt to the pouring position of the casting machine, and then pour the alloy melt into the preheated casting mold;
[0060] S3.2: The rotating magnetic field generator and the three-phase voltage regulator are placed on the left and right sides of the casting mold. After the alloy melt is poured into the casting mold, the rotating magnetic field generator and the three-phase voltage regulator are started to apply a rotating magnetic field. The rotation rate of the rotating magnetic field is 82r / s, and the rotation direction is changed once every 30s. The rotation direction of the rotating magnetic field is changed by the three-phase voltage regulator. After 5 minutes of electromagnetic treatment, the rotating magnetic field generator and the three-phase voltage regulator are turned off;
[0061] S3.3: Subsequently, water is sprayed on the outer surface of the casting mold to cool it for 80 seconds to accelerate the solidification of the alloy melt to form a casting;
[0062] S3.4: When the casting is solidified and cooled to 320°C on the surface of the casting mold, the casting is taken out of the casting mold, and the casting is placed in a resistance furnace and heated to 900°C for 3 hours. The casting is taken out of the furnace and placed in the air to cool, completing the high-temperature heat treatment;
[0063] S3.5: When the casting temperature drops to 350°C, put the casting back into the resistance furnace and heat it to 480°C. Keep it warm for 5 hours. Take the casting out of the furnace and place it in the air to cool. This completes the low-temperature heat treatment.
[0064] S3.6: When the casting temperature drops to 350°C, put the casting back into the resistance furnace and heat it to 600°C for 3 hours.
[0065] The casting is taken out of the furnace and placed in the air to cool. After the casting cools to room temperature, aluminum bronze is obtained;
[0066] S4: Hydrophobic and corrosion-resistant protective film is formed.
[0067] S4.1: The aluminum bronze is placed in a dry sandblasting machine, and 0.15 MPa compressed air and sand are introduced into the spray gun of the dry sandblasting machine to sandblast and polish the surface of the aluminum bronze to remove the oxide film on the surface of the aluminum bronze. The sandblasting is performed for 12 minutes, and then the aluminum bronze after sandblasting is ultrasonically cleaned with deionized water for 5 minutes to obtain the aluminum bronze after surface treatment;
[0068] S4.2: Place the surface treated aluminum bronze and copper plate in a 0.2 mol / L NaCl aqueous solution, with the surface treated aluminum bronze as the anode and the copper plate as the cathode. The distance between the anode and the cathode is set to 30 mm. A DC power supply is applied with a current density of 0.5 A / cm 2, magnetic stirring at 150 rpm / min, after etching for 5 minutes, the etched aluminum bronze is taken out, and ultrasonically cleaned with deionized water for 5 minutes to obtain the pretreated aluminum bronze;
[0069] S4.3: Add nickel sulfate, nickel chloride, boric acid, saccharin sodium, 1,4-butynediol and nano-silicon dioxide into deionized water, stir and mix evenly to obtain an electroplating solution, wherein the mass ratio of nickel sulfate, nickel chloride, boric acid, saccharin sodium, 1,4-butynediol, nano-silicon dioxide and deionized water is 25:6:8:1.5:13:25:300, and the particle size of the nano-silicon dioxide is 25 nm;
[0070] S4.4: Place the nickel plate and the pretreated aluminum bronze in the electroplating solution, with the nickel plate as the anode and the pretreated aluminum bronze as the cathode. Set the distance between the anode and the cathode to 30 mm, heat to 60 ° C, and pass a DC power supply so that the current density is controlled at 5A / dm 2 , magnetic stirring 200 rpm / min, electrodeposition 15 min;
[0071] S4.5: Subsequently, the electrodeposited aluminum bronze is taken out, washed twice with deionized water, and immersed in a 1 wt% ammonium ferrous sulfate ethanol solution. After soaking for 40 minutes, it is dried at 120°C under normal pressure for 20 minutes to complete the formation of a hydrophobic and corrosion-resistant protective film on the surface of the aluminum bronze, thereby obtaining high-performance aluminum bronze.
[0072] Example 2
[0073] A preparation process of high-performance aluminum bronze, wherein the mass percentage of aluminum bronze alloy components is: Al: 13.0%, Mn: 5.0%, Fe: 4.0%, Ni: 3.0%, Ti: 0.8%, B: 0.3%, Zr: 0.2%, and the balance is Cu and unavoidable impurities;
[0074] The specific steps include:
[0075] S1: Smelting,
[0076] S1.1: Weigh electrolytic copper, metallic aluminum, manganese powder, iron powder, AlTiB master alloy, nickel plate and Al-Zr master alloy according to the alloy composition ratio of high-performance aluminum bronze;
[0077] S1.2: Add electrolytic copper, metallic aluminum, manganese powder, and Al-Zr master alloy into a smelting container, and smelt in vacuum at 1260°C for 30 minutes, stirring continuously during the melting, until the electrolytic copper, manganese powder, Al-Zr master alloy, and metallic aluminum are completely melted;
[0078] S1.3: Subsequently, iron powder, nickel plate and AlTiB master alloy are added to the smelting container, and vacuum smelting is performed at 1680° C. for 20 min, with continuous stirring, until all the materials in the smelting container are melted, thereby obtaining a melt;
[0079] S2: Ultrasonic vibration treatment,
[0080] S2.1: adding a mixture of aluminum chloride, sodium chloride and aluminum oxide to the melt, introducing nitrogen into the smelting container, and refining the melt for 8 minutes, wherein the mass ratio of the melt to the mixture of aluminum chloride, sodium chloride and aluminum oxide is 1:0.003;
[0081] S2.2: During the refining process, turn on the ultrasonic drive power switch of the ultrasonic generator, immerse the ultrasonic radiation rod into the melt to a depth of 2 cm, and apply ultrasonic vibration with a power of 600 W;
[0082] S2.3: After ultrasonic vibration treatment for 3 minutes, turn off the ultrasonic drive power switch of the ultrasonic generator and remove the ultrasonic radiation rod from the melt;
[0083] S2.4: After refining, pour the refined melt into a ladle, keep it at 1400°C for 2 minutes, remove the slag, and obtain an alloy melt;
[0084] S3: pouring and heat treatment,
[0085] S3.1: Transfer the alloy melt to the pouring position of the casting machine, and then pour the alloy melt into the preheated casting mold;
[0086] S3.2: The rotating magnetic field generator and the three-phase voltage regulator are placed on the left and right sides of the casting mold. After the alloy melt is poured into the casting mold, the rotating magnetic field generator and the three-phase voltage regulator are started to apply a rotating magnetic field. The rotation rate of the rotating magnetic field is 78r / s, and the rotation direction is changed once every 60s. The rotation direction of the rotating magnetic field is changed by the three-phase voltage regulator. After 5 minutes of electromagnetic treatment, the rotating magnetic field generator and the three-phase voltage regulator are turned off;
[0087] S3.3: Subsequently, water is sprayed on the outer surface of the casting mold to cool it for 60 seconds to accelerate the solidification of the alloy melt to form a casting;
[0088] S3.4: When the casting is solidified and cooled to 300°C on the surface of the casting mold, the casting is taken out of the casting mold and placed in a resistance furnace and heated to 800°C for 1 hour. The casting is taken out of the furnace and placed in the air to cool, thus completing the high temperature heat treatment;
[0089] S3.5: When the casting temperature drops to 320°C, put the casting back into the resistance furnace and heat it to 430°C, keep it warm for 2 hours, take the casting out of the furnace and place it in the air to cool, completing the low-temperature heat treatment;
[0090] S3.6: When the casting temperature drops to 320°C, put the casting back into the resistance furnace and heat it to 520°C for 1 hour.
[0091] The casting is taken out of the furnace and placed in the air to cool. After the casting cools to room temperature, aluminum bronze is obtained;
[0092] S4: Hydrophobic and corrosion-resistant protective film is formed.
[0093] S4.1: The aluminum bronze is placed in a dry sandblasting machine, and 0.1 MPa compressed air and sand are introduced into the spray gun of the dry sandblasting machine to sandblast and polish the surface of the aluminum bronze to remove the oxide film on the surface of the aluminum bronze. The sandblasting is performed for 6 minutes, and then the aluminum bronze after sandblasting is ultrasonically cleaned with deionized water for 3 minutes to obtain the aluminum bronze after surface treatment;
[0094] S4.2: Place the surface treated aluminum bronze and copper plate in a 0.2 mol / L NaCl aqueous solution, with the surface treated aluminum bronze as the anode and the copper plate as the cathode. The distance between the anode and the cathode is set to 30 mm. A DC power supply is applied with a current density of 0.2 A / cm 2 , magnetic stirring at 100 rpm / min, after etching for 3 minutes, the etched aluminum bronze is taken out, and ultrasonically cleaned with deionized water for 3 minutes to obtain the pretreated aluminum bronze;
[0095] S4.3: Add nickel sulfate, nickel chloride, boric acid, saccharin sodium, 1,4-butynediol and nano-silicon dioxide into deionized water, stir and mix evenly to obtain an electroplating solution, wherein the mass ratio of nickel sulfate, nickel chloride, boric acid, saccharin sodium, 1,4-butynediol, nano-silicon dioxide and deionized water is 25:6:8:1.5:13:25:300, and the particle size of the nano-silicon dioxide is 25 nm;
[0096] S4.4: Place the nickel plate and the pretreated aluminum bronze in the electroplating solution, with the nickel plate as the anode and the pretreated aluminum bronze as the cathode. The distance between the anode and the cathode is set to 30 mm. Heat to 50°C and pass a DC power supply so that the current density is controlled at 4A / dm 2 , magnetic stirring 150 rpm / min, electrodeposition 10 min;
[0097] S4.5: Subsequently, the electrodeposited aluminum bronze is taken out, washed once with deionized water, and then immersed in a 1wt% ammonium ferrous sulfate ethanol solution. After soaking for 30 minutes, it is dried at 100°C under normal pressure for 15 minutes to complete the formation of a hydrophobic and corrosion-resistant protective film on the surface of the aluminum bronze, thereby obtaining high-performance aluminum bronze.
[0098] Example 3
[0099] A preparation process of high-performance aluminum bronze, wherein the mass percentage of aluminum bronze alloy components is: Al: 7.0%, Mn: 8.0%, Fe: 2.0%, Ni: 1.0%, Ti: 0.2%, B: 0.1%, Zr: 0.1%, and the balance is Cu and unavoidable impurities;
[0100] The specific steps include:
[0101] S1: Smelting,
[0102] S1.1: Weigh electrolytic copper, metallic aluminum, manganese powder, iron powder, AlTiB master alloy, nickel plate and Al-Zr master alloy according to the alloy composition ratio of high-performance aluminum bronze;
[0103] S1.2: Add electrolytic copper, metallic aluminum, manganese powder, and Al-Zr master alloy into a smelting container, and smelt in vacuum at 1320°C for 50 minutes, stirring continuously during the melting, until the electrolytic copper, manganese powder, Al-Zr master alloy, and metallic aluminum are completely melted;
[0104] S1.3: Subsequently, iron powder, nickel plate and AlTiB master alloy are added to the smelting container, and vacuum smelting is performed at 1780°C for 40 minutes, with continuous stirring, until all the materials in the smelting container are melted, thereby obtaining a melt;
[0105] S2: Ultrasonic vibration treatment,
[0106] A mixture of aluminum chloride, sodium chloride and aluminum oxide is added to the melt, nitrogen is introduced into the smelting container, and the melt is refined for 8 minutes, wherein the mass ratio of the melt to the mixture of aluminum chloride, sodium chloride and aluminum oxide is 1:0.001;
[0107] S2.2: During the refining process, turn on the ultrasonic drive power switch of the ultrasonic generator, immerse the ultrasonic radiation rod into the melt to a depth of 5 cm, and apply ultrasonic vibration with a power of 1000 W;
[0108] S2.3: After 5 minutes of ultrasonic vibration treatment, turn off the ultrasonic drive power switch of the ultrasonic generator and remove the ultrasonic radiation rod from the melt;
[0109] S2.4: After refining, pour the refined melt into a ladle, keep it at 1500°C for 7 minutes, remove the slag, and obtain an alloy melt;
[0110] S3: pouring and heat treatment,
[0111] S3.1: Transfer the alloy melt to the pouring position of the casting machine, and then pour the alloy melt into the preheated casting mold;
[0112] S3.2: The rotating magnetic field generator and the three-phase voltage regulator are placed on the left and right sides of the casting mold. After the alloy melt is poured into the casting mold, the rotating magnetic field generator and the three-phase voltage regulator are started to apply a rotating magnetic field. The rotation rate of the rotating magnetic field is 82r / s, and the rotation direction is changed once every 30s. The rotation direction of the rotating magnetic field is changed by the three-phase voltage regulator. After 5 minutes of electromagnetic treatment, the rotating magnetic field generator and the three-phase voltage regulator are turned off;
[0113] S3.3: Subsequently, water is sprayed on the outer surface of the casting mold to cool it for 80 seconds to accelerate the solidification of the alloy melt to form a casting;
[0114] S3.4: When the casting is solidified and cooled to 320°C on the surface of the casting mold, the casting is taken out of the casting mold, and the casting is placed in a resistance furnace and heated to 900°C for 3 hours. The casting is taken out of the furnace and placed in the air to cool, completing the high-temperature heat treatment;
[0115] S3.5: When the casting temperature drops to 350°C, put the casting back into the resistance furnace and heat it to 480°C. Keep it warm for 5 hours. Take the casting out of the furnace and place it in the air to cool. This completes the low-temperature heat treatment.
[0116] S3.6: When the temperature of the casting drops to 350°C, the casting is placed in the resistance furnace again and heated to 600°C, and kept at this temperature for 3 hours. The casting is taken out of the furnace and placed in the air to cool. After the casting is cooled to room temperature, aluminum bronze is obtained;
[0117] S4: Hydrophobic and corrosion-resistant protective film is formed.
[0118] S4.1: The aluminum bronze is placed in a dry sandblasting machine, and 0.15 MPa compressed air and sand are introduced into the spray gun of the dry sandblasting machine to sandblast and polish the surface of the aluminum bronze to remove the oxide film on the surface of the aluminum bronze. The sandblasting is performed for 12 minutes, and then the aluminum bronze after sandblasting is ultrasonically cleaned with deionized water for 5 minutes to obtain the aluminum bronze after surface treatment;
[0119] S4.2: Place the surface treated aluminum bronze and copper plate in a 0.2 mol / L NaCl aqueous solution, with the surface treated aluminum bronze as the anode and the copper plate as the cathode. The distance between the anode and the cathode is set to 30 mm. A DC power supply is applied with a current density of 0.5 A / cm 2 , magnetic stirring at 150 rpm / min, after etching for 5 minutes, the etched aluminum bronze is taken out, and ultrasonically cleaned with deionized water for 5 minutes to obtain the pretreated aluminum bronze;
[0120] S4.3: Add nickel sulfate, nickel chloride, boric acid, sodium saccharin, 1,4-butynediol and nano-silicon dioxide into deionized water, stir and mix evenly to obtain an electroplating solution, wherein the mass ratio of nickel sulfate, nickel chloride, boric acid, sodium saccharin, 1,4-butynediol, nano-silicon dioxide and deionized water is 20:4:3:1:7:20:200, and the particle size of the nano-silicon dioxide is 25 nm;
[0121] S4.4: Place the nickel plate and the pretreated aluminum bronze in the electroplating solution, with the nickel plate as the anode and the pretreated aluminum bronze as the cathode. Set the distance between the anode and the cathode to 30 mm, heat to 60 ° C, and pass a DC power supply so that the current density is controlled at 5A / dm 2 , magnetic stirring 200 rpm / min, electrodeposition 15 min;
[0122] S4.5: Subsequently, the electrodeposited aluminum bronze is taken out, washed twice with deionized water, and immersed in a 1 wt% ammonium ferrous sulfate ethanol solution. After soaking for 40 minutes, it is dried at 120°C under normal pressure for 20 minutes to complete the formation of a hydrophobic and corrosion-resistant protective film on the surface of the aluminum bronze, thereby obtaining high-performance aluminum bronze.
[0123] Comparative Example 1
[0124] Compared with Example 1, the difference of Comparative Example 1 is that, in the smelting process of step S1, the added smelting of Al-Zr master alloy and AlTiB master alloy is removed, so that the mass percentage content of the aluminum bronze alloy components is: Al: 9.30%, Mn: 5.0%, Fe: 4.0%, Ni: 3.0%, and the balance is Cu and unavoidable impurities. The other steps remain unchanged to prepare aluminum bronze, which is recorded as Comparative Example 1.
[0125] Comparative Example 2
[0126] Compared with Example 1, the difference of Comparative Example 2 is that, during the smelting process of step S1, the added smelting of the Al-Zr master alloy is removed, so that the mass percentage content of the aluminum bronze alloy components is: Al: 11.6%, Mn: 5.0%, Fe: 4.0%, Ni: 3.0%, Ti: 0.8%, B: 0.3%, and the balance is Cu and unavoidable impurities. The other steps remain unchanged to prepare aluminum bronze, which is recorded as Comparative Example 2.
[0127] Comparative Example 3
[0128] Compared with Example 1, the difference of Comparative Example 2 is that, during the smelting process of step S1, the added smelting of the AlTiB master alloy is removed, so that the mass percentage content of the aluminum bronze alloy components is: Al: 10.7%, Mn: 5.0%, Fe: 4.0%, Ni: 3.0%, Zr: 0.2%, and the balance is Cu and unavoidable impurities. The other steps remain unchanged to prepare aluminum bronze, which is recorded as Comparative Example 3.
[0129] Comparative Example 4
[0130] Compared with Example 1, the difference of Comparative Example 4 is that steps S2.2-S2.3 are removed, and after adding a slag remover and introducing nitrogen into the smelting container, the melt is only refined until the refining is completed, and the remaining steps remain unchanged to prepare aluminum bronze, which is recorded as Comparative Example 4.
[0131] Comparative Example 5
[0132] Compared with Example 1, the difference of Comparative Example 5 is that step S3.2 is removed, and after the alloy melt is poured into the casting mold, water is directly sprayed on the outer surface of the casting mold to cool it down, so that the alloy melt solidifies to form a casting, and the other steps remain unchanged to prepare aluminum bronze, which is recorded as Comparative Example 5.
[0133] Comparative Example 6
[0134] Compared with Example 1, the difference of Comparative Example 6 is that the nano-silicon dioxide component in the plating solution of step S4.3 is removed, and the plating solution only includes nickel sulfate, nickel chloride, boric acid, sodium saccharin, 1,4-butynediol and water. The other steps remain unchanged to prepare high-performance aluminum bronze, which is recorded as Comparative Example 6.
[0135] Performance Testing
[0136] Mechanical properties test
[0137] According to Examples 1-3 and Comparative Examples 1-5, three test samples were selected from each group of aluminum bronzes. According to the requirements of national standard GB / T228-2010, the tensile strength, elongation after fracture and hardness of each group of test samples were measured and recorded, and the tensile strength, elongation after fracture and hardness average of each group of test samples were calculated. The results are shown in Table 1.
[0138] Tensile strength(Mpa) Elongation after break (%) Hardness (HBS) Example 1 810.5 23.4 235.2 Example 2 807.3 22.6 233.8 Example 3 804.7 20.2 231.1 Comparative Example 1 683.0 15.5 174.1 Comparative Example 2 694.9 17.2 182.6 Comparative Example 3 705.1 18.0 179.5 Comparative Example 4 748.3 19.3 186.3 Comparative Example 5 740.6 19.3 181.6
[0139] Table 1
[0140] As can be seen from Table 1, the aluminum bronzes prepared in Examples 1-3 are superior to the aluminum bronzes prepared in Comparative Examples 1-5 in terms of tensile strength, elongation after fracture and hardness, indicating that the elemental components of Ti, Zr and B in the alloy melt can effectively improve the strength and toughness of the aluminum bronze, wherein Zr can synergistically react with Al to form fine dispersed intermetallic compound particles Al3Zr, which effectively hinder recrystallization and grain growth, while Ti and B can react with each other to form TiB2, which modifies the alloy microstructure, inhibits the alloy recrystallization process, and refines the alloy grains; in addition, applying ultrasonic vibration and rotating magnetic field during refining and casting solidification can also assist in improving the strength and toughness of the aluminum bronze during the preparation process of the aluminum bronze, which is beneficial to further enhance the mechanical properties of the aluminum bronze.
[0141] Corrosion resistance test
[0142] The samples of Examples 1-3 and Comparative Example 6 were grouped, and one test sample was selected from each group of high-performance aluminum bronzes. According to the requirements of the national standard GB / T10125-2021, a neutral salt spray test was performed on each group of test samples, and the test results are shown in Table 2.
[0143]
[0144]
[0145] Table 2
[0146] As shown in Table 2, the neutral salt spray resistance of the high-performance aluminum bronzes prepared in Examples 1-3 all reached a qualified level of 288h, while the neutral salt spray resistance of the high-performance aluminum bronze in Comparative Example 6 only reached a qualified level of 240h. This indicates that the hydrophobic and corrosion-resistant protective film is formed by electrodeposition on the surface of the aluminum bronze, and the nano-silicon dioxide and nickel components in the hydrophobic and corrosion-resistant protective film can cooperate with each other to play a hydrophobic and corrosion-resistant role on the aluminum bronze. Compared with the aluminum bronze with only a nickel layer electrodeposited on the surface, the high-performance aluminum bronze with a hydrophobic and corrosion-resistant protective film electrodeposited on the surface has better salt resistance, which is beneficial to improving the corrosion resistance of the high-performance aluminum bronze in seawater.
[0147] Welding quality test
[0148] According to Examples 1-3 and Comparative Example 6, groups were formed, and 2 test samples were selected from the high-performance aluminum bronzes prepared in each group. A flux was covered on the surface of each test sample, and the flux contained zinc powder, triethylenetetramine, stannous octoate and a corrosion inhibitor. Subsequently, the test samples were preheated to 220° C., and two test samples in the same group were overlapped by welding in a protective atmosphere of 99.99% argon gas. The welding current was 110A. After the temperature of the welded test samples dropped to 300° C., they were kept warm for 2 hours, and then the welded test samples were placed in the air to cool to room temperature to obtain welded finished products.
[0149] The shear strength test of the joints of each group of welded finished products was carried out by using a tensile test machine, with a load of 500KGF and a loading speed of 2mm / min. The shear strength test results of the joints of each group of welded finished products were recorded. The test results are shown in Table 3.
[0150] Joint shear strength (Mpa) Example 1 47.1 Example 2 46.8 Example 3 45.6 Comparative Example 6 34.3
[0151] Table 3
[0152] As shown in Table 3, the finished welded products obtained by welding and overlapping the high-performance aluminum bronzes of Examples 1-3 all had joint shear strengths greater than 45 MPa after the joint shear strength test, while the finished welded products obtained by welding and overlapping the high-performance aluminum bronzes of Comparative Example 6 had a joint shear strength of 34.3 MPa, which was the worst test result, indicating that after welding and overlapping, the high-performance aluminum bronzes obtained in Examples 1-3 had good weld joint strength and firmness after welding. That is, compared with aluminum bronzes with only a nickel layer deposited on the surface, a hydrophobic and corrosion-resistant protective film composed of nano-silicon dioxide and nickel composites deposited on the surface of aluminum bronze is more conducive to improving the welding quality of aluminum bronze, and the nano-silicon dioxide in the hydrophobic and corrosion-resistant protective film can improve the welding formation, that is, the welding strength, and reduce the occurrence of weld defects.
[0153] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all such improvements and changes should fall within the scope of protection of the appended claims of the present invention. Parts not described in detail in this specification belong to the prior art known to those skilled in the art.
Claims
1. A process for preparing high-performance aluminum bronze, characterized in that: The mass percentage of the alloy components of high performance aluminum bronze is: Al: 7.0-13.0%, Mn: 4.0-8.0%, Fe: 2.0-4.0%, Ni: 1.0-4.0%, Ti: 0.2-0.8%, B: 0.1-0.3%, Zr: 0.06-0.2%, and the balance is Cu and unavoidable impurities; The steps include: S1: Melting: weighing the charge according to the alloy composition ratio of aluminum bronze, the charge including electrolytic copper, metal aluminum, manganese powder, iron powder, AlTiB master alloy, nickel plate and Al-Zr master alloy, adding the charge into a melting container and melting it into a melt; S2: Ultrasonic vibration treatment, adding a slag remover to the melt for refining, performing ultrasonic vibration treatment on the melt during the refining process, and after the refining is completed, pouring the melt into a ladle, and obtaining an alloy melt after heat preservation, standing, and slag removal; S3: pouring and heat treatment, pouring the alloy melt into the casting mold, applying a rotating magnetic field on the left and right sides of the casting mold for electromagnetic treatment, then spraying water on the outer surface of the casting mold for cooling, taking the solidified casting out of the casting mold, and obtaining aluminum bronze after heat treatment; S4: Formation of a hydrophobic and corrosion-resistant protective film. After sandblasting, cleaning and etching the aluminum bronze, the nickel plate and the pretreated aluminum bronze are placed in an electroplating solution to perform an electroplating operation on the aluminum bronze. After the electroplating, the aluminum bronze is immersed in an ammonium ferrous sulfate ethanol solution and then dried to complete the formation of a hydrophobic and corrosion-resistant protective film on the surface of the aluminum bronze, thereby obtaining a high-performance aluminum bronze. Step S1: smelting, specifically comprising the following steps: S1.1: Weigh the furnace charge according to the alloy composition ratio of high-performance aluminum bronze, which includes electrolytic copper, metallic aluminum, manganese powder, iron powder, AlTiB master alloy, nickel plate and Al-Zr master alloy; S1.2: Add electrolytic copper, metallic aluminum, manganese powder, and Al-Zr master alloy into a smelting container, and smelt in vacuum at 1260-1320°C for 30-50 minutes, stirring continuously during the melting, until the electrolytic copper, manganese powder, Al-Zr master alloy, and metallic aluminum are all melted; S1.3: Subsequently, iron powder, nickel plate and AlTiB master alloy are added into the smelting container, and vacuum smelting is performed at 1600-1780° C. for 20-40 min, with continuous stirring, until all the materials in the smelting container are melted, thereby obtaining a melt; Step S2: ultrasonic vibration treatment, specifically comprising the following steps: S2.1: adding a slag remover to the melt, introducing nitrogen into the smelting container, and refining the melt for 5 to 8 minutes, wherein the mass ratio of the melt to the slag remover is 1:(0.001 to 0.003); S2.2: during the refining process, turning on the ultrasonic drive power switch of the ultrasonic generator, immersing the ultrasonic radiation rod into the melt to a depth of 2 to 5 cm, and applying ultrasonic vibration with a power of 600 to 1000 W; S2.3: After ultrasonic vibration treatment for 3 to 5 minutes, turn off the ultrasonic drive power switch of the ultrasonic generator and remove the ultrasonic radiation rod from the melt; S2.4: After refining, pour the refined melt into a ladle, keep it at 1400-1500°C for 2-7 minutes, remove the slag, and obtain an alloy melt; The slag remover in step S2.1 is at least one of calcium fluoride, aluminum chloride, sodium chloride, potassium chloride or aluminum oxide; In step S2.2, the operating frequency of the ultrasonic generator is 20-25kHz, and the maximum power is 3kW; Step S3: pouring and heat treatment, specifically comprising the following steps: S3.1: Transfer the alloy melt to the pouring position of the casting machine, and then pour the alloy melt into the preheated casting mold; S3.2: The rotating magnetic field generator and the three-phase voltage regulator are placed on the left and right sides of the casting mold. After the alloy melt is poured into the casting mold, the rotating magnetic field generator and the three-phase voltage regulator are started to apply a rotating magnetic field. The rotation rate of the rotating magnetic field is 78 to 82 r / s, and the rotation direction is changed once every 30 to 60 seconds. The rotation direction of the rotating magnetic field is changed by the three-phase voltage regulator. After electromagnetic treatment for 2 to 5 minutes, the rotating magnetic field generator and the three-phase voltage regulator are turned off; S3.3: Then, spray water on the outer surface of the casting mold to cool it for 60 to 80 seconds; S3.4: When the casting is solidified and cooled to a temperature of 300-320°C on the surface of the casting mold, the casting is taken out of the casting mold and placed in a resistance furnace and heated to 800-900°C for 1-3 hours. The casting is taken out of the furnace and placed in the air to cool, thus completing the high temperature heat treatment; S3.5: When the casting temperature drops to 320-350°C, put the casting back into the resistance furnace and heat it to 430-480°C, keep it warm for 2-5 hours, take the casting out of the furnace and place it in the air to cool, thus completing the low-temperature heat treatment; S3.6: When the temperature of the casting drops to 320-350°C, place the casting back into the resistance furnace and heat it to 520-600°C. Keep it warm for 1-3 hours. Take the casting out of the furnace and place it in the air to cool. After the casting cools to room temperature, aluminum bronze is obtained.
2. A process for preparing high performance aluminum bronze according to claim 1, characterized in that: Step S4: forming a hydrophobic and corrosion-resistant protective film, specifically comprising the following steps: S4.1: putting the aluminum bronze into a dry sandblasting machine, passing 0.1-0.15 MPa compressed air and sand material into the spray gun of the dry sandblasting machine, sandblasting and polishing the surface of the aluminum bronze for 6-12 minutes, and then ultrasonically cleaning the aluminum bronze after sandblasting and polishing with deionized water for 3-5 minutes to obtain the aluminum bronze after surface treatment; S4.2: Place the surface treated aluminum bronze and copper plate in a 0.2 mol / L NaCl aqueous solution, with the surface treated aluminum bronze as the anode and the copper plate as the cathode. The distance between the anode and the cathode is set to 30-40 mm. A DC power supply is applied with a current density of 0.2-0.5 A / cm 2 , magnetic stirring at 100-150 rpm / min, after etching for 3-5 minutes, taking out the etched aluminum bronze, and ultrasonically cleaning it with deionized water for 3-5 minutes to obtain the pretreated aluminum bronze; S4.3: Add nickel sulfate, nickel chloride, boric acid, sodium saccharin, 1,4-butynediol and nano-silicon dioxide into deionized water, stir and mix well to obtain an electroplating solution; S4.4: Place the nickel plate and the pretreated aluminum bronze in the electroplating solution, with the nickel plate as the anode and the pretreated aluminum bronze as the cathode. Set the distance between the anode and the cathode to 30-40 mm, heat to 50-60°C, and pass a DC power supply so that the current density is controlled at 4-5 A / dm 2 , magnetic stirring 150-200 rpm / min, electrodeposition 10-15 min; S4.5: Subsequently, the electrodeposited aluminum bronze is taken out, washed with deionized water for 1 to 2 times, and then immersed in an ammonium ferrous sulfate ethanol solution with a concentration of 1 wt%. After soaking for 30 to 40 minutes, it is dried at normal pressure of 100 to 120°C for 15 to 20 minutes to complete the formation of a hydrophobic and corrosion-resistant protective film on the surface of the aluminum bronze, thereby obtaining high-performance aluminum bronze.
3. A process for preparing high performance aluminum bronze according to claim 2, characterized in that: In step S4.3, the mass ratio of nickel sulfate, nickel chloride, boric acid, saccharin sodium, 1,4-butynediol, nano-silicon dioxide and deionized water is (20-25): (4-6): (3~8):(0.5~1.5):(7~13):(10~25):(200~300)。 4. A process for preparing high performance aluminum bronze according to claim 3, characterized in that: The nano-silicon dioxide used in step S4.3 has a particle size of 20 to 25 nm.
5. A high performance aluminum bronze, characterized in that: It is prepared by a preparation process of a high-performance aluminum bronze according to any one of claims 1 to 4 above.
